1995
DOI: 10.1113/jphysiol.1995.sp021002
|View full text |Cite
|
Sign up to set email alerts
|

Regional difference in the distribution of L‐NAME‐sensitive and ‐insensitive NANC relaxations in cat airway.

Abstract: 1. To investigate the distribution profile of functional inhibitory non-adrenergic noncholinergic (i-NANC) nerves and the contribution of NO to the NANC relaxation in the cat, we studied the effects of NW-nitro-L-arginine methyl ester (L-NAME) on NANC relaxation elicited by electrical field stimulation (EFS) in the trachea, bronchus and bronchiole. 2. EFS applied to the tracheal smooth muscle during contraction induced by 5-HT (10-5 M) in the presence of atropine (10-6 M) and guanethidine (10-6 M) elicited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
44
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 31 publications
5
44
0
Order By: Relevance
“…Specifically, electrical field stimulation (EFS) elicited monophasic relaxation in the trachea, confirming previous observations [5,8], but biphasic NANC relaxations, comprising an initial fast component followed by a second slow component in the bronchioles. L-NAME selectively abolished the first component of NANC relaxation without affecting the second in bronchioles, whilst, in the trachea, L-NAME completely suppressed the monophasic NANC relaxation after single or short repetitions (<5) of 1 ms pulse stimuli; however, after more stimuli (>10) of 1 or 4 ms duration, suppression of NANC relaxation was incomplete (to 40-50% of the control value) [7]. VIP antagonists partially suppressed the L-NAME-resistant NANC relaxation.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Specifically, electrical field stimulation (EFS) elicited monophasic relaxation in the trachea, confirming previous observations [5,8], but biphasic NANC relaxations, comprising an initial fast component followed by a second slow component in the bronchioles. L-NAME selectively abolished the first component of NANC relaxation without affecting the second in bronchioles, whilst, in the trachea, L-NAME completely suppressed the monophasic NANC relaxation after single or short repetitions (<5) of 1 ms pulse stimuli; however, after more stimuli (>10) of 1 or 4 ms duration, suppression of NANC relaxation was incomplete (to 40-50% of the control value) [7]. VIP antagonists partially suppressed the L-NAME-resistant NANC relaxation.…”
mentioning
confidence: 88%
“…Eur Respir J 1997; 10: 314- Neurally-mediated relaxation of airway smooth muscle in various animal species, including man, is largely nonadrenergic and noncholinergic (NANC) (see, for example, [1]). Although the neurotransmitter(s) responsible for NANC relaxation in the airways have not been conclusively identified, nitric oxide (NO) and vasoactive intestinal polypeptide (VIP) have emerged as strong candidates [2][3][4][5][6][7].In cat airway, we have shown that NANC relaxation can be classified into two components by thresholds for activation or by sensitivity to N ω -nitro-L-arginine methylester (L-NAME), and that the pattern of L-NAME-sensitive and -insensitive components differs in central and peripheral airways [6,7]. Specifically, electrical field stimulation (EFS) elicited monophasic relaxation in the trachea, confirming previous observations [5,8], but biphasic NANC relaxations, comprising an initial fast component followed by a second slow component in the bronchioles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst these, the Ca¥-dependent Cl¦ current (ICl(Ca)), which may be large enough to depolarize the membrane to the Cl¦ equilibrium potential (−30 to −20 mV; Aickin, 1990), may contribute to membrane depolarization and subsequent muscle tension development during muscarinic receptor activation (see review by Large & Wang, 1996), although the physiological significance of this mechanism in the tracheal smooth muscle remains to be determined. Nitric oxide (NO) and compounds capable of liberating NO relax various types of smooth muscle (Lincoln, 1989;Kuriyama et al 1995); this probably also applies to airway smooth muscle, where not only the pivotal role of NO in the non-adrenergic, non-cholinergic (NANC) transmission, but also strong tracheo-relaxing actions of NO-related compounds have been demonstrated (Hamaguchi et al 1992;Bialecki & Stinton-Fisher, 1995;Jing et al 1995;Takahashi et al 1995). These relaxing actions, in part, appear to be associated with membrane hyperpolarization (Hamaguchi et al 1992;Bialecki & Stinton-Fisher, 1995), which would in turn decrease Ca¥ entry through voltage-dependent Ca¥ channels (which exhibit a steep voltage dependence close to the resting membrane potential; Nelson et al 1990), although in cat tracheal smooth muscle endogenous and exogenous NO potently relax the muscle with no discernible changes in membrane potential Takahashi et al 1995).…”
mentioning
confidence: 99%
“…Nitric oxide (NO) and compounds capable of liberating NO relax various types of smooth muscle (Lincoln, 1989;Kuriyama et al 1995); this probably also applies to airway smooth muscle, where not only the pivotal role of NO in the non-adrenergic, non-cholinergic (NANC) transmission, but also strong tracheo-relaxing actions of NO-related compounds have been demonstrated (Hamaguchi et al 1992;Bialecki & Stinton-Fisher, 1995;Jing et al 1995;Takahashi et al 1995). These relaxing actions, in part, appear to be associated with membrane hyperpolarization (Hamaguchi et al 1992;Bialecki & Stinton-Fisher, 1995), which would in turn decrease Ca¥ entry through voltage-dependent Ca¥ channels (which exhibit a steep voltage dependence close to the resting membrane potential; Nelson et al 1990), although in cat tracheal smooth muscle endogenous and exogenous NO potently relax the muscle with no discernible changes in membrane potential Takahashi et al 1995). The mechanism underlying NO-induced or NO-related compound-induced hyperpolarization is likely to involve the increased activity of large-conductance, Ca¥-dependent K¤ (BK) channels (Hamaguchi et al 1992;Bialecki & StintonFisher, 1995), through increased phosphorylation of BK subunits by an altered balance between phosphatase (Zhou et al 1996) and cGMP-dependent kinase (G-kinase) activities (Robertson et al 1993;Yamakage et al 1996).…”
mentioning
confidence: 99%